TINJAUAN GABUNGAN TINDAK PIDANA MENYEBARKAN BERITA BOHONG YANG MENGAKIBATKAN KERUGIAN KONSUMEN (STUDI PUTUSAN NO. 2029 K/PID.SUS/2023): Joint Review Of The Criminal Action Of Spreading Fake News Causing Consumer Losses (Study Of Decision No. 2029 K/Pid.Sus/2023) - Muhammad Reza Ar-Raffi; Andi Widiatno Hummerson (Reformasi Hukum Trisakti, 2025)
The offense of disseminating false information can lead to consumer financial losses, as seen in the case of Indra Kesuma (Indra Kenz), who promoted quick money-making methods through Binomo, recognized in Indonesia under Decision No. 2029 K / Pid.Sus / 2023. The main problems are 1) What is the form of combined criminal acts (concursus) in the crime of spreading false news that results in consumer losses? 2) How are criminal sanctions imposed on perpetrators of criminal acts? (Study of Decision No. 2029 K / Pid.Sus / 2023). The research was analyzed qualitatively and conclusions were drawn using deductive logic. The conclusion is 1) The combined criminal acts committed by the defendant are included in the form of a combined act or concursus realis. 2) The ten-year prison sentence imposed does not align with concursus realis principles, suggesting a more appropriate charge under Article 3 of Law Number 8 of 2010 on Money Laundering, highlighting a misapplication of Law Number 11 of 2008 on Information and Electronic Transactions.